Undocumented immigrants and advanced heart failure therapies - Matthew Kogan; Sarah L. Kimball; Katherine Purrington; Jennifer Cedor; Omar K. Siddiqi, MD (JHLT Open)
This study highlights the challenges undocumented immigrants face in accessing advanced heart failure therapies, despite contributing to the organ donor pool. Some key barriers are the lack of provider awareness, social support issues, and timing constraints. The survey conducted among cardiologists at Massachusetts teaching hospitals revealed that while most providers (82.5%) refer patients with undocumented status for advanced therapies, a significant percentage (87.5%) that still perceive immigration status as a barrier to transplantation. Addressing these misconceptions through legal partnerships and enhancing provider education is crucial for improving access to life-saving treatments for undocumented patients.